About Normative Sanctities and Dissident Spiritualities - María Luisa Solís Zepeda (Ocula)
This work provides an overview into the semiotic study of Spanish mysticism (Golden Age), and distinguishes between normative mysticism, characterized by adherence to established canon and literary tradition, and another one, which deviates from the norm, particularly in the context of mysticism in New Spain. The paper discusses the case of beatas, women who were often at odds with ecclesiastical authorities due to their unconventional experiences and practices. These spiritual anomalies that germinated since that century grew exponentially towards the 20th century, so much that today religious practices and spiritualities in Mexico often seem to be made "à la carte", some even associated with criminal lifestyles. These lines expose the challenges faced by a semiotician, especially one inclined towards structural semiotics, in analyzing religious manifestations and emphasize some methodological and interdisciplinary problems.